Some Perspectives on the Migration of Skilled Professionals from Ghana - Asiedu, A.B. (Indiana University Press, 2010)
In the last four decades or so, transnational movements of both skilled and unskilled labour from developing countries to the advanced industrial economies have witnessed an unprecedented growth. Fuelled largely by deteriorating livelihood conditions in the developing world and increasing demand for wealthy and highly skilled professionals in the developed economies, these movements have attracted a lot of research attention and public policy discourses on the ‘pros and cons’ of such movements. Like others, Ghana has had a long history of movement of her nationals to various parts of the world for various reasons. However there appears to be a policy void on ways for enhancing these benefits for Ghana and this paper contributes to filling this gap. The paper discusses the merits and demerits associated with the transnational movements of Ghanaian Health and Educational professionals and proposes ways for enhancing the benefits associated with these movements for Ghana. It also suggests pathways for aiding future migration policy formulation in Ghana.
Keywords: Skilled and unskilled labour; Ghana; Health and Educational professionals